Proposta de ensino de Dinâmica adaptado ao sistema de ensino remoto com viés da aprendizagem significativa - Dourado, Marco Aurélio Rodrigues (2021)
This work is the culmination, on the part of the professor, of the completion of the Professional National Masters in Teaching in Physics, by the Federal University of Mato Grosso through the Institute of Physics, Cuiabá campus. The result was the concern to enable meaningful learning in the context of remote education, in view of the COVID-19 disease pandemic, between the months of April and May of the year two thousand and twenty-one. The educational product aims to build a dialogic relationship between the student and the teaching material mediated by the teacher, this mechanism being adapted to the online teaching environment. The product consists of a sequence of classes on the topic of Newtonian Dynamics and was applied to first-year high school students at the public school of the Governador José Frageli state network. As theoretical inspiration for the construction of the product, the authors Novak and Gowin were sought. The product was applied in fifteen online meetings through the google meet platform and the whatsapp application. The didactic sequence has two stages, the first is the construction of a concept map and video applications prepared by the author, the second stage consists of studies of the author's own texts, by synchronous meeting. Student learning assessment was based on observations of significant learning indicators through application of forms, concept maps, texts and discussions. The search for evidence of learning resorted to the qualitative methodological contribution of content analysis.